Face recognition based automated student attendance system - et. al., Babakulov Bekzod , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Face recognition technologies have gone so far in the modern world. The usage of real-time facial recognition is an efficient solution which improves the student attendance system. Previously considered inaccurate and unfinished, face recognition, driven by progress in Deep Learning, is now asserting itself as one of the most advanced biometric identification technology. Thus, many universities around the world integrate it into their teaching platforms. Face recognition is an open door to distance education too, so these programs are on the rise. It helps in conversion of the frames of the video into images so that the face of the student can be easily recognized for their attendance so that the attendance database can be easily reflected automatically